(untitled) (Construction Economics and Building, 2014)
Lack of clarity in contract documents can lead to disputes between contracting parties. Standard form contracts have evolved due to construction business becoming increasingly complex and the difficulty in drafting bespoke conditions of contract for each project. Numerous advantages have been identified in using standard forms of contract. However, clients often modify some clauses in order to include specific requirements for a project. While the consequences of ill-modifications to standard forms have been researched, no study has been done on the impact of these modifications on the clarity and readability of the document. Using 281 modified clauses from large infrastructure projects implemented in Sri Lanka, this study found that on balance modifications generally make the document more difficult to read; 60% of the sample clauses were more difficult to read compared to 40% becoming easier. More than 50% of the original and modified clauses were still at the ‘very difficult’ level of readability, which requires the equivalent of post-graduate level to understand. The study contends that modifications have not resulted in improved readability. The study highlights the necessity of clear and plain language when modifying contract documents.